Guidelines for estimating the feeding performance of diving birds - Carbone, Chris (Wildfowl, 1995)
A method of assessing the feeding performance of wild diving birds is presented that relies on the use of field data on diving behaviour and environmental conditions, and of additional information on underwater behaviour obtained from captive diving experiments. Two components of feeding performance are considered - diving efficiency (measured as the ratio of the time spent feeding over the dive cycle time) and the rate of food consumption. These two components can be used to assess habitats that differ both in water depth and food concentration. At present, however, there is limited information available on consumption rates of birds feeding on natural foods and on different substrates in the benthos. This information could be obtained from captive feeding trails.